2021
DOI: 10.1002/erv.2831
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin as a possible biomarker and maintaining factor in patients with eating disorders reporting childhood traumatic experiences

Abstract: Objective The recent conceptualization of ghrelin as a stress hormone suggested that its chronic alterations may have a role in maintaining overeating behaviors in subjects with eating disorders (EDs) reporting childhood traumatic experiences. The aim of this study was to investigate the alterations of ghrelin levels in patients with EDs, their associations with early trauma, binge and emotional eating, and possible moderation/mediation models. Method Sixty‐four patients with EDs and 42 healthy controls (HCs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Lopez-Aguilar et al 40 and Raspopow et al 41 demonstrated that impulsive and emotional eating was associated with ghrelin and cortisol dysregulation, which was suggested that emotional eating coupled with subjective feelings of hunger, might contribute to eating in response to a psychological stressor. Rossi et al 42 further revealed that ghrelin levels were positively associated with emotional eating, particularly among those who experienced childhood trauma Evidence has supported a pivotal relationship of childhood trauma with the severe mental disorders as well as severe emotional dysregulation 43 …”
Section: Discussionmentioning
confidence: 99%
“…Lopez-Aguilar et al 40 and Raspopow et al 41 demonstrated that impulsive and emotional eating was associated with ghrelin and cortisol dysregulation, which was suggested that emotional eating coupled with subjective feelings of hunger, might contribute to eating in response to a psychological stressor. Rossi et al 42 further revealed that ghrelin levels were positively associated with emotional eating, particularly among those who experienced childhood trauma Evidence has supported a pivotal relationship of childhood trauma with the severe mental disorders as well as severe emotional dysregulation 43 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, adolescent PTSD is characterized by developmental abnormalities in frontolimbic circuitry that may contribute to increasing threat reactivity, weaker emotion regulation and higher rates of internalizing symptoms, such as anxiety and depression (Herringa, 2017;Herringa et al, 2013). Disrupted neurobiological systems hypothesized to be dysregulated in traumatized ED patients are being explored (Brewerton et al, 2020a;Monteleone et al, 2019b;Murray & Holton, 2021;Rodriguez-Quiroga et al, 2021;Rossi et al, 2021). It is notable that patients in the PTSD+ group presented with significantly higher mean %MBMI than those without PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature has studied the role of traumatic events in developing EDs, even when the actual effects are still not well understood [ 9 , 10 ]. However, different studies have documented the presence of different biological scars in subjects with EDs and personal histories of maltreatment, in line with the hypothesis of a traumatic echo-phenotype of EDs [ 11 , 12 , 13 , 14 ]. According to this perspective, the COVID-19 pandemic might represent an interesting traumatic event for patients [ 15 , 16 ], that has been shared by siblings, and this might help researchers better understand individuals’ coping strategies.…”
Section: Introductionmentioning
confidence: 65%